Mathematics Educations of Helplessness - Julio Correa; João Ricardo Viola dos Santos (Prometeica, 2023)
The main objective of this paper is to present a mathematics education of helplessness in a problematization movement of political affects. So, we produce a discussion about Circuit of Affects, by the Brazilian philosopher Vladimir Safatle, in which fear and hope are constituted as affects that paralyze us and prevent us from creating new forms of life. Helplessness could be constituted as an affect for us to move with the contingency outside the temporality of expectation. The Covid-19 pandemic is used as example for our considerations in the direction of presenting, in a first draft, three concepts to think/operate a mathematics education of helplessness: scale, belonging and border. A mathematics education with Gaia between humans and non-humans in becoming movements.